The Effects of Microalgae as Live Food for Brachionus plicatilis (Rotifer) in Intensive Culture System - Abd Rahman, Abdull Razak; Che Cob, Zaidi; Jamari, Zainoddin; Mohamed, Abdul Majid; Toda, Tatsuki; Ross, Othman Haji (Penerbit Universiti Sains Malaysia, 2018)
Brachionus plicatilis is used to feed fish and crustacean larvae in the aquaculture industry. It is well established that the type of microalgae may influence rotifer production. This experiment was conducted to determine the effect of five different locally available microalgae species at Fisheries Research Institute (FRI), Kampung Pulau Sayak, Kedah, Malaysia on the instantaneous growth rate (µ) of rotifer. Nannochloris sp., Tetraselmis sp., Isochrysis sp., Chlorella sp., and Nannochloropsis sp. were used as feed at different algae densities (0.1, 0.3, 0.7 and 1.5 × 106 cells/ml) and culture volumes (20, 70 and 210 ml). At algae densities ranging from 0.3 to 1.5 × 106 cells/ml, an average µ value of more than 0.90 per day were recorded for all algae species. However, at density of 0.1 × 106 cells/ml, only Tetraselmis sp. resulted in the significantly highest µ value compared with others (p < 0.05). In terms of volume, smaller culture volume of Tetraselmis sp. (20 ml) showed significantly higher µ compared with higher volume (70 and 210 ml cultures).